The Effect of Brand Awareness and Perceived Quality on User Loyalty Through Satisfaction as a Mediating Variable - Didin, Didin (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to analyze the effect of Brand Awareness and Perceived Quality on the loyalty of Zahir Accounting Online users, with satisfaction as a mediating variable. The background of this study refers to the importance of building loyalty in an increasingly competitive digital accounting software market, where Brand Awareness and perceived quality are major factors in consumer decisions. The research uses a quantitative method with Partial Least Square Structural Equation Modeling (PLS-SEM) analysis, based on data from 60 respondents who are users of Zahir Accounting Online. The results show that Brand Awareness and Perceived Quality have a positive and significant effect on loyalty, and user satisfaction partially mediates this relationship. The R² value of 0.657 indicates that this model can explain 65.7% of user loyalty variance, indicating strong predictive power. These findings support Aaker’s theory on the role of Brand Awareness and Perceived Quality in brand equity, as well as Oliver’s theory on satisfaction as a link to consumer loyalty. This study emphasizes the importance of strategies to increase brand awareness, service quality, and user satisfaction as keys to maintaining the loyalty of digital accounting application users.